FUNGSI TARI JEPIN SILAT DESA ARANG LIMBUNG KECAMATAN SUNGAI RAYA KABUPATEN KUBU RAYA KALIMANTAN BARAT - Sari, Ratih Mulia; Mering, Aloysius; Ismunandar, Ismunandar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The purpose of this research are 1) to describe the function of Jepin Silat Dance at Arang Limbung village 2) to describe the implementation of the research finding’s function of Jepin Silat Dance at Arang Limbung village ini Art and Culture Subject at senior high school.Jepin Silat Dance is belonging intoconsolation dance because its present the beauty of motion that could entertain people and as a hobby of Arang Limbung society. The function of performance of Jepin Silat dance as well as its character in performing the great preparation is needed and had to pay more attention at the beauty motion itself. It can be seen the participating of Jepin Silat dance at The Traditional Dance of Kalimantan Barat and at several competition that have been followed. The social function of Jepin Silat dance is to strengthen the social relation. The social function could be seen when the audience looked on Jepin Silat dance and the comunication happened, also there a sense of solidarity each the dancer in successing their performanceKeywords: Function, Jepin Silat Dance at Arang Limbung village